Corn Cost-Return Budget in North Central Kansas - Warmann, Gerald W.; Dhuyvetter, Kevin C. (My University, 1996)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_1996_10
Keywords: MF2161; Crops; Economics; MF